The Role of Organelle Stresses in Diabetes Mellitus and Obesity: Implication for Treatment - Yi-Cheng Chang; Siow-Wey Hee; Meng-Lun Hsieh; Yung-Ming Jeng; Lee-Ming Chuang (Analytical Cellular Pathology)
The type 2 diabetes pandemic in recent decades is a huge global health threat. This pandemic is primarily attributed to the surplus of nutrients and the increased prevalence of obesity worldwide. In contrast, calorie restriction and weight reduction can drastically prevent type 2 diabetes, indicating a central role of nutrient excess in the development of diabetes. Recently, the molecular links between excessive nutrients, organelle stress, and development of metabolic disease have been extensively studied. Specifically, excessive nutrients trigger endoplasmic reticulum stress and increase the production of mitochondrial reactive oxygen species, leading to activation of stress signaling pathway, inflammatory response, lipogenesis, and pancreatic beta-cell death. Autophagy is required for clearance of hepatic lipid clearance, alleviation of pancreatic beta-cell stress, and white adipocyte differentiation. ROS scavengers, chemical chaperones, and autophagy activators have demonstrated promising effects for the treatment of insulin resistance and diabetes in preclinical models. Further results from clinical trials are eagerly awaited.